Descriptive study on the usefulness of early hospital consultation for newborns at-risk (Spain) (Archives of Pediatrics of Uruguay, 2026)
Introduction: a healthy newborn goes through a series of processes that usually stabilize in the first 48-72 hours. After discharge they are usually assessed at their health center in the first week of life, but some patients with borderline discharge criteria (weight, jaundice, feeding difficulties) should be evaluated in the following 24-48 hours. In our pediatric center we had a neonate at-risk consultation. We believe this to be is a beneficial measure for patients that can also prevent an overload of primary care. Our goal with this study is to describe the use of this consultation.Methodology: a retrospective, descriptive study was designed to include all the consultations carried out in 2022. Maternal and patient characteristics, reason for consultation and subsequent evolution are described.Results: 254 consultations took place in one year. 46 patients presented weight loss after discharge and required some type of intervention (initiation of supplementation, frenectomy and new follow-up). Twenty-six patients required admission (20 for hyperbilirubinemia, 4 for hyperbilirubinemia and weight loss and 2 for weight loss).Conclusions: an early hospital follow-up in neonates at risk enables a close control of pathologies such as hyperbilirubinemia and significant weight loss, which are frequent reasons for admission in the first days of life.
Keywords: Newborn; Primary Health Care; Spain